1986
DOI: 10.1152/ajpheart.1986.251.4.h693
|View full text |Cite
|
Sign up to set email alerts
|

O2 radicals in arachidonate-induced increased blood-brain barrier permeability to proteins

Abstract: We studied the effect of topical application of arachidonate on the brain surface on blood-brain barrier permeability to either 125I-labeled human albumin or to horseradish peroxidase administered intravenously. Arachidonate was applied under a cranial window, and the concentration of albumin was measured in brain after elimination of the blood by perfusion-fixation. Permeability to 125I-labeled albumin was increased in the superficial 4 mm of the cortex but not in the deeper cortical layer 4-6 mm from the sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
36
2

Year Published

1987
1987
2002
2002

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 0 publications
3
36
2
Order By: Relevance
“…For example, it was hypothesized that acute elevations of blood pressure after injury in the adult result in the release and metabolism of arachidonic acid, which would generate oxygen free radicals, causing cerebral functional abnormalities. 27,31,32,35 However, in contrast to studies performed in adult and juvenile animals, there was no acute elevation in blood pressure after FPI in the newborn pig. 8 Because the elevation in systemic blood pressure was thought to be an absolute requirement for cerebral generation of free radicals after injury, 27,31,32,35 the observed decrease in blood pressure was perplexing initially.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…For example, it was hypothesized that acute elevations of blood pressure after injury in the adult result in the release and metabolism of arachidonic acid, which would generate oxygen free radicals, causing cerebral functional abnormalities. 27,31,32,35 However, in contrast to studies performed in adult and juvenile animals, there was no acute elevation in blood pressure after FPI in the newborn pig. 8 Because the elevation in systemic blood pressure was thought to be an absolute requirement for cerebral generation of free radicals after injury, 27,31,32,35 the observed decrease in blood pressure was perplexing initially.…”
Section: Discussioncontrasting
confidence: 64%
“…31 In that study, the sustained dilation and abnormal responsiveness of pial arterioles observed after injury could be reversed by treatment with the free radical scavengers SOD and catalase. 31 Oxygen radicals also have been shown to increase blood-brain barrier permeability, 32 produce ultrastructural changes in pial vessel endothelium, 32 and cause abnormal arteriolar reactivity. 33 In addition, oxygen radical scavengers have been shown to improve vascular function and blood flow during focal ischemia in rats, which may account for the observed reductions in infarct size.…”
Section: Discussionmentioning
confidence: 99%
“…the rate at which SOD converts the superoxide anion to HµOµ. These two antioxidants were also needed to block induced increases in albumin extravasation seen by Wei et al (1986). Desferrioxamine also prevented the permeability response to arachidonic acid at modest concentrations (100 ìÒ rather than > 1 mÒ), which relates to its ability to prevent lipid peroxidation rather than direct free radical formation (Caraceni, Vanthiel & Borle, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, blockade of AT 1 receptors could also decrease the stimulation of superoxide and peroxynitrite production by Ang II in blood vessels. 25,26 Superoxide ion formation by Ang II could produce cytotoxic effects, including increases in blood-brain barrier permeability, 27 and this may explain the decrease in cerebral edema after candesartan pretreatment. In addition, peripheral administration of candesartan inhibits AT 1 receptor binding in brain areas such as the nucleus of the solitary tract, contributing to regulate cerebrovascular flow through modulation of central sympathetic activity and in turn modulation of the brain Ang II system 12,28 and in the middle cerebral artery.…”
Section: Nishimura Et Al At 1 Antagonist Reduces Cerebral Ischemiamentioning
confidence: 99%